The Impact of Tax and Welfare Policieson Employment and Unemployment in OECD Countries - Disney, Richard (IMF Working Papers; Working Paper, 2000)
The paper provides a selective survey of methods and findings concerning the impact of tax and welfare policies on employment, unemployment, and economic growth in OECD countries. The paper examines a number of facets of tax and welfare policy and concludes that cross-country macroeconomic studies shed only limited light on the issue. Analyses of household behavior using microeconometric methods are much more fruitful but the question remains of how to aggregate these results to assess the overall impact of policy.